(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Davydova A.A. Keywords: Astrakhan Press, Astrakhan journalism, the world picture, provincial periodicals. The article describes the history of the Astrakhan Press (1905-1907). The paper analyzes the themes and issues of Astrakhan journalism, covers the specifics of the information in the world picture of provincial periodicals revolutionary times. Considerable space is devoted to the Astrakhan national press.